UJI KEEFEKTIFAN PUPUK BIOKOMPOS “ Trichosubur Protect “ TERHADAP PERTUMBUHAN BIBIT KAKAO ( Theobroma Cacao L ) - Evisilvia Evisilvia; Umrah Umrah; Yusran Yusran (Biocelebes, 2018)
Research on the effectivenes of the test biokompos ’’ Trichosubur Protect’’on the growth of the cacao plant seeds have been conducted from November 2015 through march 2016 at the cacao gardens hortus Botanicus ( Botanical Garden ) department of Biology, Faculty of Mathematics and Natural Sciences Tadulako University, Palu- Central Sulawesi. The objective is to determine the dose biokompos “ Trichosubur Protect “ which is effective against the growth of cacao seedlings. The study was designed in a compososition of the treament as fllows : P0 ( Basal medium without “ Trichosubur Protect “),P1 ( Basic medium + ’’ Trichosubur Protect “ 10 g), P2 ( basic medium + “ Trichosubur Protect “ 20 g), P3 ( Basic medium + “ Trichosubur Protect “ 30 g), P4 ( Basic medium + “ Trichosubur Protect” 40 g), P5 ( medium Ground + NPK 2 g). Basic media used in the form of a mixture of soil 19 kg + 1 kg of rice husk, put in a polybag 25 x 30 cm 13 kg as the planting of cacao. Parameters include observavation every week; seedling height (cm), number of leaves ( leaf),the girth (mm).observation at harvest inculude: Biomassa (g),leaf weight (g),the weight rod (g), root weight(g),and root dry weight (g). The result shwed that treament P4 ( basic + “ Trichosubur Protect “ 40 g) the treatment is more efeective when seen from the results of last observatoins covering, the everage 29,07 cm plant height, leaf number 40 strands, stem diameter 3,73 cm, weight of leaves at harvest time 12,03 g ( Moisture in the leaves 44,30 g ),weight at harvest stalks of 7,62 g( moisture in the trunk 56,30 g), root weight at harvest 5,93g ( Moisture at the root of 92,80 g), the weight of biomassa when harvested 27,22 g, 4,42 g dry weight of leaf, stem dry weight of 1,98 g, 8,06 g dry weight biomassa.